Multi-species detection using multi-mode absorption spectroscopy (MUMAS) - Northern, J; Thompson, A; Hamilton, M; Ewart, P (2013)
The detection of multiple species using a single laser and single detector employing multi-mode absorption spectroscopy (MUMAS) is reported. An in-house constructed, diode-pumped, Er:Yb:glass micro-laser operating at 1,565 nm with 10 modes separated by 18 GHz was used to record MUMAS signals in a gas mixture containing CH, NO and CO. The components of the mixture were detected simultaneously by identifying multiple transitions in each of the species. By using temperature- and pressure-dependent modelled spectral fits to the data, partial pressures of each species in the mixture were determined with an uncertainty of ±2 %. © 2013 Springer-Verlag Berlin Heidelberg.